Análisis de los Procesos Centrados al Paciente en el Área de Radiología: Un Enfoque Orientado al Modelado de Procesos de Negocio - Navor-Galeana., N. P.; Gutiérrez Martínez, J.; Martínez Licona., F. M.; Molina Salazar., R. (Revista Mexicana de Ingenieria Biomedica, 2013)
In recent years, a set of tools for processes modeling have been developed, that was originally designed for the industrial environment, and that up to date has not been widely applied in healthcare environment. This paper presents the implementation of the processes analysis of outpatients and inpatients care attended in the radiology department of the National Institute of Rehabilitation in Mexico City, applying the business processes modeling notation (BPMN), which showed through the use of workflow indexes, that the attention processes duration for emergency patients (7.87±4.50 min/study) was lower when compared to the special studies patients (53.96±13.12 min/study), as well as the using time of medical radiological technology and the sequence of activities of the personnel involved in the processes. In addition, it was possible to identify the variables that influence the realization time of radiological studies (age and physical condition), being age the one with the greatest statistical significance for the realization time of emergency studies (p = 0.004). The application of BPMN in health processes provides a supporting tool for continuous improvement, resources optimization and identification limiting factors in the processes of care medical services.